If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + -7a = (3a + -3) Reorder the terms: 23 + -7a = (-3 + 3a) Remove parenthesis around (-3 + 3a) 23 + -7a = -3 + 3a Solving 23 + -7a = -3 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 23 + -7a + -3a = -3 + 3a + -3a Combine like terms: -7a + -3a = -10a 23 + -10a = -3 + 3a + -3a Combine like terms: 3a + -3a = 0 23 + -10a = -3 + 0 23 + -10a = -3 Add '-23' to each side of the equation. 23 + -23 + -10a = -3 + -23 Combine like terms: 23 + -23 = 0 0 + -10a = -3 + -23 -10a = -3 + -23 Combine like terms: -3 + -23 = -26 -10a = -26 Divide each side by '-10'. a = 2.6 Simplifying a = 2.6
| 5y-8+y=41+4y-5y | | 35+17= | | 3f=2 | | -10+(-31)= | | 4(x-3)=16x+12 | | p+6=11 | | 6x+4y+2= | | 9x+8=7x+10 | | 4x+3+3x=8x+3-x | | 3[5(y-3)+9]-2(8y-1)= | | y=-1E-05x | | 3x^2+5x-250=0 | | x/9=172 | | -18+(-6)= | | x^2+1x-156=0 | | 5x+14=2x+8 | | 2x-60=40 | | 22=5x+3x^2 | | 3x-2=3x+17 | | 22+15= | | -4(x+6)+6=6(x+3)+6 | | -10+(-3)= | | 37-5x=7-8x | | X*3+1=6 | | 2x^2+6x+7=o | | -4(y-3y)+2=-6(2y-y)+4+13y | | 2x-3+3x-10=132 | | X-5y=32 | | abs(3x+5)=1 | | 3b-2b=2-2b | | 3x+4=2+7 | | 3y+13=-1 |